2010
DOI: 10.4102/aveh.v69i1.120
|View full text |Cite
|
Sign up to set email alerts
|

Optometric education at Westville: past, present and future

Abstract: This article presents historical information, current activities and future plans with regards to optometric education at the Department of Optometry, Westville campus of the University of Kwa-Zulu-Natal (UKZN) in Durban. The Department, established in 1979 under the political dispensation of apartheid was intended to cater to the needs of Indian students but now admits students of all races. Also, it has been developing in every aspect of optometric education, staffing and facilities. The undergraduate optome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This study found that mainly black people (73%) and Indian people (37%) comprised the sample. Historically, the School of Optometry at UKZN, has been training mainly black and Indian optometrists since the programme's inception in 1980 35 ; thus, a larger representation of these population groups is expected. Most conspicuous is the lack of white and mixed-race optometrists in public service in KZN.…”
Section: Discussion Demographymentioning
confidence: 99%
“…This study found that mainly black people (73%) and Indian people (37%) comprised the sample. Historically, the School of Optometry at UKZN, has been training mainly black and Indian optometrists since the programme's inception in 1980 35 ; thus, a larger representation of these population groups is expected. Most conspicuous is the lack of white and mixed-race optometrists in public service in KZN.…”
Section: Discussion Demographymentioning
confidence: 99%
“…The University of KwaZulu-Natal (UKZN), which is located in KwaZulu-Natal, South Africa, is one of four higher education institutions that provide optometry education and training in South Africa. As part of the facilities and aligned to the community engagement and teaching and learning agendas of UKZN, the university-based eye clinic aims to provide affordable eye care services to the public, especially previously disadvantaged communities, throughout the academic year (Mashige, 2010). The clinic serves as a referral centre for patients from KwaZulu-Natal and surrounding areas.…”
Section: Introductionmentioning
confidence: 99%